Literature Review: Analysis of the Role of the Board of Commissioners and the Audit Committee in Supervising the Implementation of Good Corporate Governance - Manao, Marcella; Aini, Nurul; Sari Lubis, Nurmala; Maisyarah, Renny (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This study seeks to broaden understanding of the strategic roles played by the Board of Commissioners and the Audit Committee in executing Good Corporate Governance (GCG) across various companies in Indonesia. Through a literature review approach, this research assessed multiple relevant journals to pinpoint factors influencing successful oversight by these entities. The findings reveal that autonomy of members, frequency of meetings, and the professional experience of members of both the Board of Commissioners and the Audit Committee are pivotal in enhancing corporate governance quality. Moreover, the study highlights challenges in GCG implementation, such as members' limited independence and skills, as well as restrictions in the frequency and quality of oversight. Consequently, the study suggests strengthening the structure and capabilities of the Board of Commissioners and Audit Committee as strategic measures for achieving superior and sustainable corporate governance, while also boosting transparency and accountability in an increasingly competitive market. It is hoped that this research will contribute to the evolution of GCG policies and practices in Indonesia and serve as a reference for future research in the corporate governance field.